2019
DOI: 10.1097/mrr.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a high-intensity rapid access outpatient stroke rehabilitation program

Abstract: A common strategy to improve cost-effectiveness in healthcare is to offer outpatient care instead of in-hospital care. Toronto Rehabilitation Institute developed an outpatient high-intensity fast-track (FT) stroke rehabilitation program aimed at discharging inpatient stroke rehabilitation patients earlier or bypassing inpatient rehabilitation altogether. This cost-effectiveness analysis compares FT rehabilitation within 1 week of discharge with no FT in a single healthcare payer system. Patient costs and outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…Multidisciplinary interventions included a range of interventions such as integrated rehabilitation services (n = 8), [29][30][31][32][33][34][35][36] extra rehabilitation care (n = 3), [37][38][39] rehabilitation team treatment, and fast-track specialized services (n = 6). [40][41][42][43][44][45] Fifteen studies were conducted in high-income countries (n = 1) in low-income country and (n = 1) in middle-income country. Thirteen studies focused on stroke on patients with TBI (n = 3) and ABI (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary interventions included a range of interventions such as integrated rehabilitation services (n = 8), [29][30][31][32][33][34][35][36] extra rehabilitation care (n = 3), [37][38][39] rehabilitation team treatment, and fast-track specialized services (n = 6). [40][41][42][43][44][45] Fifteen studies were conducted in high-income countries (n = 1) in low-income country and (n = 1) in middle-income country. Thirteen studies focused on stroke on patients with TBI (n = 3) and ABI (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3 studies [37][38][39] involving extra rehabilitation care reported cost savings ranging from £329 to £1889. A total of 4 studies [41][42][43][44] concluded that fast-track specialized services were cheaper and more cost-effective than usual care, with cost savings ranging from £253 to £6063 (costs converted to price year 2020 sterling prices). For instance, Grieve et al 41 found that "fast-track early" transfer to a neuroscience center was associated with lower mortality (odds ratio 0.52, 95% CI 0.34-0.80) and higher quality of life for survivors (mean gain 0.13, 95% CI 0.032-0.225) but positive incremental costs (£15 001, 95% CI £11 123-£18 880) compared with late or no transfer.…”
Section: Resultsmentioning
confidence: 99%
“…However, early initiation of rehabilitation is limited by several barriers [25]. Tam et al [26] used a rapid access outpatient stroke rehabilitation program for providing rehabilitation. This approach could alleviate problems such as rehabilitation unavailability and the inability to treat patients in the hospital for a long period.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between the cost of implementing physical activity and exercise-based rehabilitation programs versus the clinical and economic gains from e.g., lowered productivity losses and reduced need for hospitalizations and medication remains to be evaluated in transplant recipients. However, exercise-based rehabilitation has been shown to be cost-effective in many other chronic disease populations [123,124].…”
Section: Political Contextmentioning
confidence: 99%